Neuerwerbung einer äthiopischen Handschrift durch die Staatsbibliothek zu Berlin, Preußischer Kulturbesitz - Six, Veronika (Aethiopica, 2003)
Description of an Ethiopic manuscript with texts of mainly magical content and design. The manuscript was acquired very recently by the Staatsbibliothek zu Berlin, Preußischer Kulturbesitz.